PENGUATAN IDENTITAS SEKOLAH KATOLIK MELALUI PENERAPAN PROGRAM PASTORAL SEKOLAH DI SMAK ST THOMAS AQUINO MOJOKERTO - Poto, Maria Kumala Mutiara; Permana, Natalis Sukma (CREDENDUM: Jurnal Pendidikan Agama, 2024)
This research aims to determine the efforts of Catholic schools, especially SMAK St. Thomas Aquino Mojokerto in carring out the process of strengthening the identity of Catholic schools, especially through school pastoral programs. Strengthening the identity of Catholic schools is a means of integrating the values of the Catholic faith. Integrating the values of the Catholic faith can be done through a school pastoral program implemented with the aim of helping students become familiar with the teachings of the Catholic faith and forming good character of the students. In this research the author uses a qualitative approach focusing with a case study method. Research data collection was carried out using observation, interview and documentation techniques. The research data analysis was carried out using a condensation approach.The results of research show that the school pastoral program is a means of strengthening the identity of Catholic schools at SMAK St.Thomas Aquino Mojokerto. Through this school's pastoral program, the Catholic values in the form of faith in God, social values of justice, morality, intellectual values and love have been taught to students at SMAK St. Thomas Aquino Mojokerto aims of strengthening the identity of this Catholic school.